Analisis Mutu dan Gizi Produk Biskuit Biji Nangka Sebagai Alternatif Makanan Pendamping Asi pada Balita - Dyah Ayu Pradnya Paramitha (PT FORMOSA CENDEKIA GLOBAL, 2022)
Biscuits are one of the processed food products made from wheat flour, biscuits are quite popular among the public. Biscuits are a type of pastry made from a hard dough, flat in shape, when broken, the cross section of the piece has a dense texture, can be high or low in fat. Biscuits are made from wheat flour which is added with other additives, such as sugar, eggs, margarine, and flavorings. Complementary foods of sufficient quality and quantity affect the physical growth and intelligence of children. Jackfruit seeds contain good carbohydrates and calories when consumed by humans, especially for children during their growth period such as toddlers.